ChemInform Abstract: Compositionally Tunable Photoluminescence Emission in Cu2ZnSn(S1‐xSex)4 Nanocrystals. Issue 49 (3rd December 2013) - Singh, Ajay; Singh, Shalini; Levcenko, Sergiu; Unold, Thomas; Laffir, Fathima; Ryan, Kevin M.
Abstract Wurtzite‐type Cu2ZnSn(S1‐xSex)4 (x = 0—1) nanocrystals are synthesized from mixtures of Cu(acac)2, Zn(OAc)2, Sn(OAc)4, dodecanethiol, diphenyl diselenide, trioctylphosphine oxide, and octadecene (Ar flow, 155 °C, 15 min).